Study of factors affecting resolution of urinary tract infection following treatment of constipation in Iranian children who visited a tertiary referral hospital - Imanzadeh, Farid; Sayyari, Ali-Akbar; Sharifian, Mostafa; Javaherizadeh, Hazhir; Aghasi, Parisa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2012)
Aim : The aim of this study was to evaluate the effect of sex, age, number of urinary tract infections, and duration of constipation on resolution of urinary tract infection (UTI) following treatment of constipation in Iranian children referred to pediatric gastroenterology and pediatric nephrology clinics. Material and methods : This study was conducted in Mofid Children’s Hospital. Duration of the study was from 1 October 2010 to 31 June 2011. In this study every child who visited due to urinary tract infection or constipation was asked about the other condition. Data were analyzed by SPSS ver. 16.0 (Chicago, IL, USA). χ 2 and t-test were used for comparison. Results : In this study, 550 children visited the hospital due to urinary tract infection or constipation. Finally 380 patients with constipation and UTI were detected. Among 220 patients with UTI > 2 times, 90 (40.90%) showed UTI resolution after treatment of constipation. Of 160 patients with  2 UTIs, 85 (53.12%) showed UTI improvement following treatment of constipation (p = 0.018). In children younger than 1 year, treatment of UTI after treatment of constipation was more effective than in other ages (p < 0.001). There was no significant difference between males and females. In children with constipation duration less than 6 months, most cases of urinary tract infection resolved after treatment of constipation (p < 0.001). Conclusions : The UTI resolution after treatment of constipation was higher in children < 1 year old. If the patient has a history of more than 2 UTIs, improvement of UTI following treatment of constipation will be decreased.